From Svyatoslav I to Ivan IV: milestones of gaining rulership in the mythopoeic images of the “Kazan History” - Aksanov A.V. (Золотоордынское обозрение)
The purpose of the study: To study the stages of the acquisitions of the Orthodox kingdom in the narrative of the author of the “Kazan History”. Research materials: Historiographical sources, Russian chronicles, historical writings, diplomatic documents, etc. Results and scientific novelty: Previously, researchers have already addressed the problem of studying the concept of gaining the kingdom, presented in the “Kazan History”. It was found that the author of the “Kazan History” compared the capture of Kazan in 1552 with the conquest of Constantinople in 1453. Through this ideological parallel, the chronicler tried to show that the capture of Kazan became a key and final milestone in the struggle of the Rurik Dynasty for the acquisition of the larger kingdom. The history of the conquest of the Kazan Khanate and the associated idea of the liberation of Russia from Tatar domination was also considered. However, the researchers ignored the pre-Horde period of the struggle for the royal regalia and the problem of its correlation with the idea of gaining the kingdom through the capture of Kazan. As a result of this study, it was found that the concept of gaining the kingdom also had a pre-Ordinal component semantically related to the conquest of the “Kazan Khanate through Constantinople” plots. The mythopoeic comparison of Kazan with Constantinople allowed the chronicler to make Prince Svyatoslav Igorevich, who achieved great victories over the Greeks, the founder of the struggle for the kingdom. The victories of Svyatoslav I and Vladimir I became the foundation for the acquisition of the royal crown by Vladimir Monomakh. Similarly, the activities of Ivan III and Vasily III led to the capture of Kazan and the new acquisition of the kingdom by Ivan IV.